Cutaneous injuries of complicated herpes zoster in an elderly immunocompetent patient - Farias, Luis Arthur Brasil Gadelha; Pires Neto, Roberto da Justa (Journal of Health & Biological Sciences, 2017)
A 81-years-old caucasian man presented with acute burning pain in external auricular region and inside the auditory canal of right ear, associated with vesicular lesions on face, jugal and lingual mucosa. Physical examination revealed vesicular lesions in external auricular region and inside the auditory canal. Red blood cell count, leukocytes and platelets were normal. Presented HIV-1 and 2 both negative. Patient denied previous history of Diabetes and Hypertension. Treatment was initiated with Ceftriaxone 2g, Acyclovir 250mg, Prednisone 60mg and Bicarbonate Water for rinsing. After eight days of hospitalization, patient reported hearing loss in the right ear, chewing difficulty and mild pain in face. Auditory hearing loss and hypoacusis may suggest involvement of vestibulocochlear nerve. Figure 1 shows cicatricial crusted lesions following trigeminal nerve mandibular branch trajetory. Figure 2 reveals cicatricial crusted lesions following trigeminal nerve maxilar branch, trigeminal branch and erythematous scarring lesions in tongue, hypoglossal nerve region. Figure 3 reveals small crusted lesions following the trigeminal ophthalmic branch. Herpes zoster is caused by Varicella zoster virus (VZV) reactivation in individuals who had Varicella in childhood or who were vaccinated. The presence of more than one dermatome affected is rare in immunocompetent individuals, being more prevalent in immunosuppressed individuals such as HIV positive and transplanted patients. 1 Disseminated herpes zoster can occur in any immunocompetent patient but predominates in elderly due to factors that compromise cellular immune response. 2,3